The impact of social media on the values of contemporary Chinese adolescents: a case study of the role of platform Douyin in a shaping cultural identity - Li, Wang; Saladounikava, Tatiana V. (Journal of the Belarusian State University. Journalism, 2026)
This article analyses the impact of the short video platform Douyin (the Chinese version of TikTok) on the formation of young people’s cultural identity and values. It examines the influence of Douyin’s recommendation algorithms and user-generated content on adolescents’ values through various forms of communication. It concludes that Douyin facilitates the formation of local cultural identity but also carries potential risks (such as an information cocoon effect and the development of a monotheistic personality structure). It is noted that these problems may limit adolescents’ access to cultural diversity, which, in turn, can lead to a narrowing of their worldview.